Determinants of corporate reputation: a study of consumers’ perspective of Malaysian Aviation Company - Tay, Su-Lin; Chan, Tak-Jie; Mohd Hassan, Nurul` Ain (Human Resource Management Academic Research Society, 2020)
This study examined the predicting factors of selected facets of RepTrak™ reputation model (products/services, innovation, citizenship, leadership, performance) and corporate reputation of Malaysia Airlines Berhad, from consumers’ perspective. Utilizing the Fombrun’s (2006) RepTrakTM reputation model, this model served as a guide to the study. Survey questionnaires were used to gather the data, in which the researchers distributed the questionnaires online and in-person to the Malaysia Airlines consumers who had prior encounters with the airline company. A 173 valid responses were yielded as the results. The collected data was then analysed through Pearson’s Product-Moment Correlation and Multiple Regression using Statistical Package for the Social Sciences (SPSS) version 24.0. The findings of the Pearson’s product-moment correlation analysis showed that the associations between product and services, innovation, citizenship, performance, and corporate reputation have a significantly positive moderate relationship. Meanwhile, the correlations between leadership and corporate reputation have a significantly positive high relationship. In addition, multiple regression analysis revealed that products/services, innovation, citizenship, leadership, and performance were the significant predicting variables, which explained 71.9 % of the variance of corporate reputation. Conclusion, limitations, suggestions, and implications of this study were discussed.